The Effect of Profitability and Capital Structure on Company Value in Property and Real Estate Sector Companies Listed on The Indonesia Stock Exchange (IDX) - Fitria Awaliyah; Dini Arifian; D Muhammad Yamin (Edupedia Publisher, 2025)
Company value is investors' perception of the company's level of success in managing resources which is reflected in the company. Company value is very important for companies to improve the welfare of their owners by increasing company value. This research aims to determine whether profitability and capital structure can influence company value. Profitability is measured by ROE, Capital Structure is measured by DER and Company Value is measured by PBV. The method used in this research is a quantitative research method. The population used was all Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange (BEI) and the sample taken using the purposive sampling method was 13 companies. Data collection obtained through secondary data with documentation methods in the form of financial reports. The data analysis techniques used in this research are Descriptive Statistics, Classical Assumption Test, Multiple Linear Regression Analysis Test, Correlation Analysis Test, Coefficient of Determination Test and Hypothesis Test. The results of the analysis carried out show that partially Profitability (ROE) has a significant effect on Company Value (PBV), so H1 is accepted. Capital Structure (DER) has a significant effect on Company Value (PBV), so H2 is accepted. And simultaneously Profitability (ROE) and Capital Structure (DER) have a significant effect on Company Value (PBV), so H3 is accepted.